Blockade of CD26 Signaling Inhibits Human Osteoclast Development. (November 2014) - Nishida, Hiroko; Suzuki, Hiroshi; Madokoro, Hiroko; Hayashi, Mutsumi; Morimoto, Chikao; Sakamoto, Michiie; Yamada, Taketo
Abstract Bone remodeling is maintained by the delicate balance between osteoblasts (OBs) and osteoclasts (OCs). However, the role of CD26 in regulating bone remodeling has not yet been characterized. We herein show that CD26 is preferentially expressed on normal human OCs and is intensely expressed on activated human OCs in osteolytic bone alterations. Macrophage‐colony stimulating factor (M‐CSF) and soluble receptor activator of NF‐κB ligand (sRANKL) induced human OC differentiation, in association with CD26 expression on monocyte‐macrophage lineage cells. CD26 expression was accompanied by increased phosphorylation of p38 mitogen‐activated protein kinase (p38 MAPK), which is crucial for early human OC differentiation. The humanized anti‐CD26 monoclonal antibody, huCD26mAb, impaired the formation and function of tartrate‐resistant acid phosphatase (TRAP)/CD26 positive multi‐nucleated (nuclei > 3) OCs with maturation in the manner of dose‐dependency. It was revealed that huCD26mAb inhibits early OC differentiation via the inactivation of MKK3/6, p38 MAPK and subsequent dephosphorylation of microphthalmia‐associated transcription factor (mi/Mitf). These inhibitions occur immediately after RANKL binds to RANK on the human OC precursor cells and were demonstrated using the OC functional assays. huCD26mAb subsequently impaired OC maturation and bone resorption by suppressing the expression of TRAP and OC fusion proteins. In addition, p38 MAPK inhibitor also strongly inhibited OC formation and function. Our results suggest that the blockade of CD26 signaling impairs the development of human functional OCs by inhibiting p38 MAPK‐mi/Mitf phosphorylation pathway and that targeting human OCs with huCD26mAb may have therapeutic potential for the treatment of osteolytic lesions following metastasis to alleviate bone destruction and reduce total skeletal‐related events (SREs). © 2014 American Society for Bone and Mineral Research.